Spiritualitas Kyai Abdul Karim-Lirboyo (Sebuah Keteledanan Dari Kyai Sederhana Yang Penuh Ketawadlu’an Pendiri Pesantren Lirboyo Kediri Jawa Timur) - Saiful Mujab; Muhammad Zuhdi; Abu Syamsudin (Spiritualita, 2019)
This paper will outline the important side of a pesantren, namely "spirituality". Specifically, this study will examine the sirrah (life story) of the founder of the largest Salaf pesantren in Indonesia, namely Lirboyo-Kediri. He is K.H. Abdul Karim. The research hopefully would like give a useful description of the exemplary and spirituality of the kyai Abdul Karim to the dear readers. based on field observations, interviews with various sources and written literature this research was built. Finally, the author will present this research with descriptive narrative.